2013
DOI: 10.1111/1440-1630.12022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dimensions of home that impact on home modification decision making

Abstract: An understanding of the dimensions of home that impact decision making provides occupational therapists with a greater appreciation of the experience of home and allows them to enhance the effectiveness and acceptance of home modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 25 publications
0
70
0
Order By: Relevance
“…However, this repurposing of existing domestic space for rehabilitation activities did not necessarily lead to the medicalisation of home (Aplin et al 2013;Tamm 1999;Moore et al 2010). Rather, the separation of the rehabilitation room from the rest of the home space was fluid and, at times, blurry -in the 'rehab' room, a basket of unfolded laundry awaited folding, and memorabilia injected a sense of self-expression, collective identity, and biographical history (Tanner et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this repurposing of existing domestic space for rehabilitation activities did not necessarily lead to the medicalisation of home (Aplin et al 2013;Tamm 1999;Moore et al 2010). Rather, the separation of the rehabilitation room from the rest of the home space was fluid and, at times, blurry -in the 'rehab' room, a basket of unfolded laundry awaited folding, and memorabilia injected a sense of self-expression, collective identity, and biographical history (Tanner et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, while these ideas emphasise the stability of home, these are places that are dynamic, negotiated, and contested. Experiences of home may change from therapeutic to nontherapeutic -even detrimental -for an individual during illness or upon the onset of a chronic condition that leads to bodily limitations , for their informal carers (Donovan and Williams 2007), and for those who must adapt to home modifications (Aplin et al 2013;Tanner et al 2008).…”
Section: Therapeutic Landscapes and Homementioning
confidence: 99%
“…Boyle et al (2014) thus concluded that occupational therapists participating in the study felt that grants officers found it difficult to accept autistic children have problems which could lead to a need for an adaptation. a specific concern highlighted by families is the lack of provision for change (aplin, de Jonge, and Gustafsson 2013;Heywood 2004;Roy et al 2008), which is particularly pertinent in relation to growing children and the length of time adaptations often take to be put in place. Heywood's (2004) research took a retrospective look at disabled adaptations and her findings led her to conclude that some adaptations were not always appropriate for the long-term needs of the child, because the needs of the child changed over time.…”
Section: Service User Perspectives Of Home Adaptationsmentioning
confidence: 99%
“…To be able to remain living at home despite disabilities and being in need of care, changes to the built home environment might be necessary. When people consider altering their homes, studies have indicated that the aesthetics of the adaptation, costs associated with the installation, available space in the home and considerations about the future (such as health changes and the resale value) all affect the decision to have the house adapted [6]. When altering the home, the meaning of the home can change and it might be necessary to change habits and learn new routines for daily activities [7].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have explored the applicants' experiences of HAs [19] and home modifications [6,20], studies with an explicit focus on the cohabitants´ or caregivers´ expectations and experiences of sharing home where HAs have been made are lacking. Considering that the informal caregiver is, to a large extent, the spouse of the person in need of care, this knowledge is important when designing a person-centred HA intervention which also might facilitate caregiving tasks.…”
Section: Introductionmentioning
confidence: 99%